PENGARUH DISIPLIN KERJA, PELATIHAN DAN KEPUASAN KERJA TERHADAP PRESTASI KERJA KARYAWAN (Studi Kausal Pada Perusahaan Asuransi PT.A.J Sequislife Jakarta) - Baehaki, Mohamad Kiki; Faisal, Ahmad (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
The development of the times at this time goes so fast. One area that is quite influential in the field ofHuman Resources. The purpose of this study is to explain the influence of work discipline in sequislife insurancecompanies. The following is included with the training where a series of activities are designed to improve theskills, knowledge, experience, or changes in an individual's attitude in ways to improve the quality of servicesand products and communicate with employees or customers. Both of these elements will influence theincreasing satisfaction and work performance of employees. The data of this study get some importantconclusions that the two elements are very important for employees in an effort to improve employeesatisfaction and work performance in the work environment. Keywords: work discipline, training, job satisfaction, insurance company, employee performance